ONLINE PUBLIC ACCESS CATALOG ( OPAC ) BERBASIS SLIMS AKASIA SEBAGAI SARANA TEMU KEMBALI INFORMASI DI UPT PERPUSTAKAAN UIN PALEMBANG - Clarita, Nadya Arianty (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
In my research in this article, I discussed SLIMS ACACIA as an information retrieval system used in the library of University UIN Raden Fatah Palembang. In this article, we will convey about the application of SLIMS ACACIA in helping to search for information at UIN Raden Fatah PALEMBANG. The research method used in the completion of this article is to use qualitative methods with interview and observation data collection techniques. Interviewing is an activity carried out to obtain information directly from informants, while observation, is one of the tools used in data collection. The results of this study show that the application of SLIMS ACACIA in assisting the search for information at UIN Raden Fatah Palembang in accessing information about the availability of collections and data in the library can already help users.